Mortality Among Homeless Adults in Boston: Shifts in Causes of Death Over a 15-year Period - Baggett, Travis P. (2013)
BACKGROUND: Homeless persons experience excess mortality, but U.S.-based studies on this topic are outdated or lack information about causes of death. No studies have examined shifts in causes of death for this population over time. METHODS: We assessed all-cause and cause-specific mortality rates in a cohort of 28,033 adults aged 18 years or older who were seen at Boston Health Care for the Homeless Program between January 1, 2003, and December 31, 2008. Deaths were identified through probabilistic linkage to the Massachusetts death occurrence files. We compared mortality rates in this cohort to rates in the 2003–08 Massachusetts population and a 1988–93 cohort of homeless adults in Boston using standardized rate ratios with 95% confidence intervals. RESULTS: 1,302 deaths occurred during 90,450 person-years of observation. Drug overdose (n=219), cancer (n=206), and heart disease (n=203) were the major causes of death. Drug overdose accounted for one-third of deaths among adults <45 years old. Opioids were implicated in 81% of overdose deaths. Mortality rates were higher among whites than non-whites. Compared to Massachusetts adults, mortality disparities were most pronounced among younger individuals, with rates about 9-fold higher in 25–44 year olds and 4.5-fold higher in 45–64 year olds. In comparison to 1988–93, reductions in HIV deaths were offset by 3- and 2-fold increases in deaths due to drug overdose and psychoactive substance use disorders, resulting in no significant difference in overall mortality. CONCLUSIONS: The all-cause mortality rate among homeless adults in Boston remains high and unchanged since 1988–93 despite a major interim expansion in clinical services. Drug overdose has replaced HIV as the emerging epidemic. Interventions to reduce mortality in this population should include behavioral health integration into primary medical care, public health initiatives to prevent and reverse drug overdose, and social policy measures to end homelessness.